Evolution of theoretical views on the history of military libraries - A. M. Panchenko (Библиосфера, 2014)
In article theoretical aspects of history of military libraries in the Russian army are covered. Evolution of the main conceptual terms is presented and analyzed. The role of librarians (S. D. Maslovskij, A. R. Voynich-Syanozhetskij, A. S. Latsinskij) of the military department in developing some theoretical aspects of military library science is shown.